The use of a score-based protocol in pediatric appendicitis decreases CT scan utilization when evaluating children in a community hospital - Frieda Hulka; Bryn Morris; Paige Elliott; Bogna Targonska (SpringerOpen, 2021)
Abstract Background The Pediatric Appendicitis Score (PAS) is a validated scoring system assessing children with abdominal pain. Prior to 2016, children with abdominal pain in our community hospital were evaluated primarily using CT scans. A protocol using PAS and ultrasound (US) as the primary radiologic modality was adopted in 2016 for evaluating children with abdominal pain. The protocol consisted of three tiers with low PAS requiring no radiologic evaluation; moderate PAS requiring US and high PAS requiring initial surgical consultation. Retrospective chart review of children presenting with clinically suspected appendicitis was performed from January 2015 through December 2017, representing 1 year before and 2 years after implementation of PAS protocol. PAS scoring was assigned retrospectively to patients not scored in the emergency physician's note, and statistical analysis of the patient cohorts was performed using SPSS, version 17. This study was approved by the University of Nevada Institutional Review Board. Results Application of PAS scoring system increased use of US as the primary radiologic test from 59% pre-protocol to 91% post protocol and decreased use of CT scans from 41 to 8% (p < .05). Physician adherence to protocol improved from 59 to 71%, increasing further to 81% in the 2nd year post-protocol (p < .05). The highest rate of non-compliance was noted when providers ordered an US in patients with a low PAS, followed by ordering any radiologic tests in patients with a high PAS. Conclusion Implementation of PAS-based protocol altered clinician behavior in a community hospital when evaluating children with clinically suspected appendicitis. Improved adherence to the protocol over time with significant decrease of CT scans ordered thereby reducing radiation exposure in the pediatric population. Future improvements will be aimed at decreasing radiologic testing in patients with a low PAS and involving surgeons earlier with patients who have a high PAS as clinical acceptance to the protocol matures.